2022
DOI: 10.3389/fpsyg.2021.773492
|View full text |Cite
|
Sign up to set email alerts
|

Parent Provision of Choice Is a Key Component of Autonomy Support in Predicting Child Executive Function Skills

Abstract: Although previous work has linked parent autonomy support to the development of children’s executive function (EF) skills, the role of specific autonomy-supportive behaviors has not been thoroughly investigated. We compiled data from four preschool-age samples in the Midwestern United States (N = 366; M age = 44.26 months; 72% non-Hispanic White, 19% Black/African American, 5% Multiracial) to examine three relevant autonomy-supportive behaviors (supporting competence, positive verbalizations, and offering choi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Previous research points to a robust association between autonomy-supportive parenting and early childhood EF, above and beyond other positive parenting behaviors (Valcan et al, 2018), although longitudinal associations are not always found (Hughes et al, 2020). As reviewed in Castelo et al (2022), my students and I found this relation includes fathers and homeless families. Furthermore, we discovered that autonomy-supportive behaviors mediate the concurrent link between a parent’s own EF and their child’s EF, supporting the idea of intergenerational transmission of self-regulation through parenting behaviors (Deater-Deckard, 2014).…”
Section: Autonomymentioning
confidence: 85%
See 2 more Smart Citations
“…Previous research points to a robust association between autonomy-supportive parenting and early childhood EF, above and beyond other positive parenting behaviors (Valcan et al, 2018), although longitudinal associations are not always found (Hughes et al, 2020). As reviewed in Castelo et al (2022), my students and I found this relation includes fathers and homeless families. Furthermore, we discovered that autonomy-supportive behaviors mediate the concurrent link between a parent’s own EF and their child’s EF, supporting the idea of intergenerational transmission of self-regulation through parenting behaviors (Deater-Deckard, 2014).…”
Section: Autonomymentioning
confidence: 85%
“…This pertained across mothers and fathers and diverse race and SES samples, with correlations ranging from .22 to .43. The Supporting Competence subscale of autonomy support also was significantly related to child EF, however, only the Offering Choice subscale predicted children’s EF over and above age and the other autonomy support subscales (Castelo et al, 2022). Hence, although positive and autonomy-supportive parenting behaviors tend to co-occur, to the extent that they can be disentangled, provision of choice appears to play a key role for EF development.…”
Section: Choicementioning
confidence: 94%
See 1 more Smart Citation
“…In the light of the above, we can consider the role of caregivers as a particularly important aspect of the child's environment, as they have the potential to moderate the dynamic interactions between the child and their environmental context (Bronfenbrenner, 1977, 2005). Several studies have illustrated that a parenting style which values child autonomy, taking the child's perspective, and providing them with choices is associated with higher child EF performance (Castelo et al, 2021; Distefano et al, 2018; Meuwissen & Carlson, 2019), while educators who foster goodness‐of‐fit in relationships with children by adjusting their teaching approach to match the temperament and interests of each individual child, lay the foundations for strong cognitive and social–emotional development (Driscoll & Pianta, 2010; Keogh, 1986; O'Connor et al, 2014; Vandenbroucke et al, 2018). Consistent with this, frustration induced in classroom settings has been shown to generate intra‐individual differences in actualised EF sufficient to overshadow underlying differences in upper‐limit EF (Pnevmatikos & Trikkaliotis, 2013), while high self‐reported levels of school belonging are associated with higher working memory performance among adolescents (Wang et al, 2021).…”
Section: The Caregiver As a Possible Moderator Of Diversity In Child–...mentioning
confidence: 99%
“…Parents rated on these dimensions might be instructed to let the child do as much as he/she can, and help only when needed (Meuwissen and Carlson, 2018). This rating system has been employed in several studies (Bernier et al, 2010;Matte-Gagné and Bernier, 2011;Whipple et al, 2011;Matte-Gagné et al, 2013;Meuwissen and Carlson, 2015, 2018, 2019Distefano et al, 2018), and autonomy supportive parenting has been linked to children's improved executive functioning and academic achievement (Bernier et al, 2010;Fay-Stammbach et al, 2014;Bindman et al, 2015;Distefano et al, 2018;Castelo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%